2012
DOI: 10.1007/s00213-012-2724-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of amphetamine exposure on outcome-selective Pavlovian-instrumental transfer in rats

Abstract: Rationale Repeated exposure to psychostimulants alters behavioral responses to reward-related cues; however, the motivational underpinnings of this effect have not been fully characterized. Objectives The following study was designed to examine how amphetamine sensitization affects performance in rats on a series of Pavlovian and operant tasks that distinguish between general-incentive and outcome-selective forms of conditioned responses. Methods Adult male rats underwent Pavlovian and instrumental trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…A key recent study (Shiflett, 2012) has demonstrated that drug exposure selectively enhances general PIT effects, while it abolishes specific transfer (Fig. 2a).…”
Section: Altered Model-free and Model-based Representations By Cocainmentioning
confidence: 89%
“…A key recent study (Shiflett, 2012) has demonstrated that drug exposure selectively enhances general PIT effects, while it abolishes specific transfer (Fig. 2a).…”
Section: Altered Model-free and Model-based Representations By Cocainmentioning
confidence: 89%
“…For example, Corbit and Janak (2007b) trained rats in a specific PIT design with alcohol and sucrose reward and found that, whereas the sucrose stimulus generated the expected specific transfer effect, enhancing responding for sucrose but not alcohol, the same was not true for the alcohol stimulus which was found to enhance both responses in a manner reminiscent of general transfer (see also Shiflett 2012). The specificity of PIT in alcoholics, as well as the direct effects of alcohol stimuli on alcohol seeking, would be of significant interest for future study.…”
Section: Exposure To Drugs Of Abusementioning
confidence: 94%
“…Dopamine appears to be somewhat less important for the outcome-selective version of PIT. For example, Yin et al (2006) found that hyperdopaminergic mice failed to show elevated outcome-specific PIT, relative to wild type control mice (see also, Shiflett, 2012). Furthermore, Ostlund and Maidment (2012) reported that dopamine antagonists did not influence the ability of CSs to bias action selection for a specific outcome.…”
Section: Neural Mechanisms Of Pavlovian Reward Cue Processingmentioning
confidence: 99%